Doing research in the Global South: Exploring research ethics and their transformative potential - Leonie Tuitjer (Spatial transformation: Processes, strategies, research design, 2022)
At the conference on 'Spatial Transformation: Processes, Concepts and Research Designs', a number of local and regional case studies from spatial research were presented alongside research papers about transformation processes conducted in the so-called Global South. This short article offers a reflection on the role of research ethics and their potentially transformative power within such contexts. First, the article argues that within research projects conducted by researchers from the socalled Global North in the Global South, a critical self-reflection of ones' own position is necessary, as the researcher will inevitably be confronted with various ethical, logistical, and political challenges. Second, it is argued that it is precisely these challenges that enable critical self-reflection and the development of a transformative potential at the personal, institutional, project and output level. Research on spatial transformations may benefit from such ethico-political moments as those proposed by the social scientist Vinay Gidwani to achieve a deeper level of ethical self-reflection and perhaps a transformation on the level of knowledge production.
urn:nbn:de:0156-08910989; hdl:10419/251347; https://econpapers.repec.org/RePEc:zbw:arlfob:19
Keywords: 710; Research ethics; transformative potential; Global South; power relations